2015
DOI: 10.2528/pierl15011602
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Cancellation Method Based on Unitary Transformation of Coupled Transmission Lines-Channel Transmission Matrix

Abstract: Abstract-Crosstalk is one of the bottlenecks for high-speed circuits to increase its rate and density. In order to make tradeoff between complexity and effect of the crosstalk cancellation circuit, a crosstalk cancellation method based on unitary transformation is proposed. In the method, two unitary matrixes are obtained by Singular Value Decomposition (SVD) of coupled transmission lines-channel transmission matrix (CTL-CTM), and then according to the form of the unitary matrixes, the crosstalk canceling circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The eye The simulation results clarify that the proposed method is capable of achieving non-crosstalk in the high-speed interconnects, which suppresses the jitter and noise of crosstalk. At the same time, comparing the method in this paper with in [12][13][14] can be concluded that the circuit architecture advantage is simpler, and crosstalk cancelation effect is pretty good, easier to implement, and lower in cost under the premise of having the same signal transmission effect.…”
Section: Simulation Results and Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…The eye The simulation results clarify that the proposed method is capable of achieving non-crosstalk in the high-speed interconnects, which suppresses the jitter and noise of crosstalk. At the same time, comparing the method in this paper with in [12][13][14] can be concluded that the circuit architecture advantage is simpler, and crosstalk cancelation effect is pretty good, easier to implement, and lower in cost under the premise of having the same signal transmission effect.…”
Section: Simulation Results and Analysismentioning
confidence: 80%
“…The common purpose of two methods is to reduce the impact of crosstalk on the entire interconnect system, namely to eliminate interference from crosstalk to useful signals. Based on these, [14], constructing inverse matrix with the mathematical point to eliminate interference from crosstalk to normal signal, studied the establishment of a coupled transmission lineschannel transmission matrix on the interconnection system, in which crosstalk cancelation method that is simpler in circuit and better in effect for two coupled microstrip lines has been given. However, in the CTL-CTM established by this method, the attenuation caused by the crosstalk coupling to the local signal is not considered because the transfer function is approximated.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the specific expression of CTL-CTM, the crosstalk cancellation scheme between parallel microstrip lines [11] can be transplanted into the complex interconnection structure for crosstalk cancellation. First, eigenvalue decomposition is made to the CTL-CTM matrix in the complex interconnected structure.…”
Section: Crosstalk Cancellation Methodsmentioning
confidence: 99%
“…In this paper, crosstalk cancellation in Figures 1(b) and 1(c) is studied on the basis of a parallel microstrip interconnection structure. The CTL-CTM and crosstalk cancellation circuit of the complex interconnection structure are established through the crosstalk cancellation method of parallel microstrip lines based on CTL-CTM [11] to the complex interconnection. The usage of the crosstalk-coupling coefficient of the parallel-coupling microstrip lines is equivalent to that of the complex interconnection structure.…”
Section: Introductionmentioning
confidence: 99%
“…Crosstalk in aggressor line will become larger when multiple aggressor lines aggress one victim line especially in bus circuit model. There are many ways to reduce crosstalk on victim lines, such as reducing electromagnetic coupling between transmission lines to suppress crosstalk [4][5][6][7][8], or processing signals on transmission lines to reduce crosstalk [9][10][11]. The above solutions are commonly implemented by reducing the influence of crosstalk on the whole interconnection system, i.e., by eliminating interference of crosstalk on useful signals, but they are applied only to the 2PAM signals.…”
Section: Introductionmentioning
confidence: 99%